Altered cytokine and chemokine profile linked to autoantibody and pathogen reactivity in mothers of autistic children - McLellan, Janna; Croen, Lisa; Iosif, Ana-Maria; Yoshida, Cathleen; Ashwood, Paul; Yolken, Robert H.; Van de Water, Judy (Frontiers in Psychiatry, 2024)
Maternal autoimmunity, and more specifically, the production of specific maternal autoantibodies, has been associated with altered offspring neurodevelopment. Maternal autoantibody-related (MAR) autism is a subtype of autism that is linked to gestational exposure to certain combinations of autoantibodies to proteins known to be important for fetal neurodevelopment. We wanted to address whether mothers with autism-specific patterns of autoantibodies have a skewed cytokine and chemokine profile during an immune response to infection. To do so, we examined a subset of mothers from the Early Markers for Autism (EMA) study who either produced known patterns of MAR autoantibodies (MAR+) or did not (MAR-). We compared the cytokine/chemokine profiles of MAR+ and MAR- mothers in the context of positive immunoglobulin G (IgG) reactivity to several viral and parasitic agents. We observed that MAR+ mothers have a higher level of proinflammatory cytokine interferon-gamma regardless of IgG status. Additionally, when comparing MAR+ and MAR- mothers in the context of the different pathogens, MAR+ mothers consistently had increases in multiple proinflammatory cytokines and chemokines.